Awareness on the implementation of life cycle assessment in light industries - Tuan Ahmad, Tuan Noorunnazifah (2009)
As environmental awareness increases, industries and businesses are assessing how their activities affect the environment. Society has become concerned about the issues of natural resource depletion and environmental degradation. Many businesses have responded to this awareness by providing “greener” products and using “greener” processes. Life cycle assessment (LCA) is a systematic approach used to manage the potential environmental impacts of product and services system. This study looked into awareness of LCA among the manufacturers in Taman Universiti, Skudai,Johor and willingness to perform LCA in their company. The data obtained for this study was through surveying where the questionnaires had been distributed among the manufacturers in the study area. The analysis was done by using SPSS software. From the result, only 31.25 percent of the respondents have knowledge on LCA and 68.75 percent not having the idea about LCA. Meanwhile 40.6 percent of the respondents agree to consider performing LCA in their company and 59.4 percent not being sure. Due to lack of information on LCA, 81.25 percent agree that government should provide more training and information. However, there was a significant correlation (r=-0.358), (p<= 0.05) between respondents position and awareness of LCA at 95% significant level. The level of awareness of LCA depends on the position of the respondent. In this case, manager has higher awareness about LCA compare to others.